A new species of fishing spider Dolomedes Latreille 1804 (Araneae Pisauridae) from the Philippines - Barrion, Alberto T. (Philippines Rushing Water Publishers, 1995)
"Dolomedes mindigoetmopasi n. sp., the second species of the genus known from Luzon Island, Philippines is described and illustrated."
Keywords: Spiders -- Philippines; Pisauridae; Dolomedes; Dolomedes mendigoetmopasi n. sp